2017
DOI: 10.1038/s41598-017-01308-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparing mortality risk of patients with acute hip fractures admitted to a major trauma centre on a weekday or weekend

Abstract: Proximal femoral fractures are a major public health concern with estimated annual direct and social costs amounting to £2 billion and average 30-day mortality risk of 7.5%. In response to the recent debate over out-of-hours hospital provision we investigated the ‘weekend effect’ at a major trauma centre, caring for acute injuries. A single centre, multi-surgeon review of 2060 patients performed. The distribution of patient and treatment variables compared in patients admitted on a weekday or the weekend. Fewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…Our results are in line with a recent single-center study by Nandra et al 14 However, this study was performed in a major tertiary referral center, providing high-level trauma care allied with 7-day working rotas. Pincus et al also found no relationship between the timing of surgical procedures for hip fracture and adverse outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are in line with a recent single-center study by Nandra et al 14 However, this study was performed in a major tertiary referral center, providing high-level trauma care allied with 7-day working rotas. Pincus et al also found no relationship between the timing of surgical procedures for hip fracture and adverse outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, discharge on a Sunday or out of hours was associated with a 51.5% and 17.4% increase in 30-day mortality, respectively. Although our study did not report mortality rate by days of the week and association of mortality with day of discharge, our findings of an absence of a 'weekend effect' in hip fracture patients is in agreement with that of Nandra et al [20], which showed a reduced mortality with weekend admissions compared with weekday. This study also reported a higher mortality risk in patients with cognitive decline and pre-existing co-morbidities.…”
Section: Strengths and Weaknesses In Relation To Other Studiessupporting
confidence: 92%
“…They could not show a significant difference in the mortality for patients coming in on weekdays or weekends. There was a slightly higher mortality on weekdays than on weekends (10,2% vs. 9,7% on weekends), and specific in respect to day of the week (12,96% Monday vs. 8,06% Thursday) [16].…”
Section: Discussionmentioning
confidence: 99%